2019
DOI: 10.18295/squmj.2019.19.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Obstetrical Outcomes and Complications in Pregnant Women after Bariatric Surgery

Abstract: Bariatric surgery (BS) is a novel treatment for weight reduction with longer lasting health benefits. This review aimed to summarise the available evidence regarding the fetomaternal outcomes and the most common challenges and complications in pregnancies following BS. Google Scholar (Google LLC, Mountain View, California, USA) and PubMed<sup>®</sup> (National Library of Medicine, Bethesda, Maryland, USA) databases were searched for articles published until December 2018. A total of 64 articles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
1
11
0
1
Order By: Relevance
“…The analysis presented an increase in the number of CS, from 24.3% to 31.9%, with a decrease in urgent CS of 5%. Most studies present an increase in the rate of CS after bariatric surgery [12,20], although some researchers observed the opposite [2]. In our study, we also observed an increase in number of scheduled CS with a decrease in proportion of urgent CS.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The analysis presented an increase in the number of CS, from 24.3% to 31.9%, with a decrease in urgent CS of 5%. Most studies present an increase in the rate of CS after bariatric surgery [12,20], although some researchers observed the opposite [2]. In our study, we also observed an increase in number of scheduled CS with a decrease in proportion of urgent CS.…”
Section: Discussionsupporting
confidence: 72%
“…They can also influence the incidence and course of pregnancy-induced co-morbidities. Bariatric surgery is known to have influence on the pregnancy and neonatal outcomes, increasing the rate of small for gestational age (SGA) infants and maternal anemia and decreasing the risk of GDM, PIH and large for gestational age infants (LGA) infants [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…8 The surrounding literature is growing but remains weak, especially regarding the long-term effect on the children born to women who underwent MBS. [9][10][11][12][13] Consistent results show that MBS is associated with a reduced risk of gestational diabetes, 14,15 LGA neonates, hypertensive disorders, 16,17 and delivery outcomes; 18 however, the benefit to the newborn remains debated considering the potential risk of preterm birth and small for gestational age (SGA) infants. 14,19 Whether MBS has other benefits or risks remains largely unknown.…”
mentioning
confidence: 99%
“…BS and the following reduction of body weight leads to an important decrease in the rate of GDM, when compared to the obese population, and in some studies even to the general non-obese population. The vast majority of studies on the influence of BS on the pregnancy course confirm a significant reduction in the incidence of GDM after BS [ 30 , 42 , 70 , 71 ]. Johansson et al found a more than three-fold reduction of the incidence of GDM in patients after BS compared to the obese population, and the results were corroborated in an analysis by Burke et al [ 44 , 72 ].…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%